Evaluation of the Efficacy of Nusinersen Treatment in Patients with Late-onset SMA Using the Hammersmith Functional Motor Scale Expanded - Yiğithan Güzin; Ayşe Özbay Yıldız; Bakiye Tunçay; Pınar Gençpınar; Figen Baydan; Nihal Olgaç Dündar (Galenos Publishing House, 2024)
Objective: Spinal muscular atrophy (SMA) is a hereditary disorder with progressive muscle weakness and atrophy. Nusinersen is an antisense oligonucleotide directed against SMN2 and has been shown in studies to improve the motor skills of patients. The aim of this study was to evaluate the efficacy of nusinersen treatment in patients with SMA type 2 and type 3 using the Hammersmith Functional Motor Scale Expanded (HFMSE) score. Method: The diagnosis and differentiation of SMA type 2 and type 3 were based on clinical findings and genetic tests. The HFMSE scores of all patients were evaluated in detail before nusinersen doses. Results: Evaluation was made of a total of 15 patients, 12 SMA type 2 and 3 SMA type 3, with a median age of 13 years. None of the patients had regression of acquired abilities after nusinersen treatment. The median HFMSE score of SMA type 2 patients before treatment was 9. After nine doses of nusinersen, the HFMSE score showed a significant increase from 9 to 30 points. Although none of the patients could walk, their motor skills improved significantly. The median HFMSE score of SMA type 3 patients before treatment was 60. After 3 doses of nusinersen treatment, HFMSE scores were found to be 63. Conclusion: Nusinersen is an effective and safe treatment for patients with late-onset SMA. It can be suggested that different motor scales should be applied and developed for SMA type 2 (sitter) and type 3 (walker) patients due to differences in the clinical characteristics of SMA types.